Probiotic potential of Lactic Acid Bacteria (LAB) isolated from tempoyak made of Malaysian durian musang king, fermented chillies and budu / Nur Syazwani Alias - Alias, Nur Syazwani (2015)
Probiotic refer to live microorganism that provides beneficial effect on the host. Lactic acid bacteria (LAB) are probiotic bacteria that play critical role in food production and health maintenance. The research of probiotic bacteria have become increasing interest worldwide nowadays. However, the lacking of the studies have been reported in the isolation LAB from tempoyak made from Malaysian DOOan Musang King, fermented chillies and budu on screening its ability to pose stress environment condition that role as probiotic in human health. The objectives of this study are to screen the probiotic potential of LAB isolated from three different Malaysian fermented foods. Seven LABs have been isolated from sample after they were grown on MRS agar that has been supplemented with CaC03. All the LAB was undergo identification with respect on colony morphology, gram staining and biochemical characterization. The screening for probiotic potential of the isolated LAB was represented the survival abilities of isolated LAB in varying stress condition such as in acid environment , high and low temperature and also sodium chloride (NaCl) environment using streaking plate method on MRS agar and also using spectrophotometer to obtain the absorbance value. Lactose utilization test also was done by observing the color changes of the medium. All seven isolated LAB was identified as Lactobacillus plantarum 1 Leuconostoc mesenteroides ssp dextracium 2, Pediococcus pentosaceus and Lactobacillus plantarum 1 from tempoyak sample, Lactobacillus plantarum 1 and Lactobacillus fructivorans from fermented chillies sample, last is Weissella cibaria from budu sample. All of the isolated LAB showed the ability in resistant the wide range of stress condition environment that are in pH, NaCI condition and in critical temperature and also proved the acid production on lactose utilization test. Therefore, this study reveals that all isolated LAB has positive impact and high potential for their selection as probiotic bacteria in providing various beneficial effect on human health and can also to be commercialization in the food product.